PEMAKNAAN PERKAWINAN (STUDI KASUS PADA PEREMPUAN LAJANG YANG BEKERJADI KECAMATAN BULUKERTO KABUPATEN WONOGIRI) - Lindha Pradhipti Oktarina; Mahendra Wijaya; Argyo Demartoto (Jurnal Analisa Sosiologi, 2015)
Marriage is one of human cultures and being apart of the life cycle. It’s a base of forming a family. In ancient era, marriage was considered as conventionally, means women did the marriage because of the culture and society’s persepective. Along with the times growing, changes in the way of human thinking began. Marriage was not only considered as a must in cultural, but it became a personal and rational choice of women. A single woman started to express herself to be involved in many public media, to make her being educated and reach the higher level to catch her desire. Marriage now becomes an important thing, but it’s not the main priority.The purpose of this research is to find the meaning of marriage for a single women workers, social condition of single woman with their job, and marriage preparation of single women. Theory to analize this problem is interpretative understanding of Weber. This is a qualitative research by using case study research strategy, located in Bulukerto district. Sampling technique was purposive sampling. Data collection technique was interview. Data validity using source triangulation and method triangulation.Data analizing technique using interactive analysis model.Research result and discussion analysis showed that women have started to move on the increasing and progress of prosperity in many fields.  Including on the education quality. The involvement of women on the public sphere have opened a new discourse on their way of thinking. This influence on meaning on a perception friction about the meaning of marriage. Single women perception about their life partner is influenced by internal and exsternal factor.  Marriage is considered as an individual freedom right. Social condition of single woman toward her job can be seen from their condition of hard working, achievement of goals, focus on profession, high awarenesss of profession and carrier chances, improvement of work, appreciation of work, and discipline of work. While marriage preparation of single women is to set their life partner criteria, ideal time of marriage, settled and psikologycal readiness, and to make a pre-marital agreement. Keywords: Marriage, Single, Working Women